The Influence of Visionary Leadership and Communication Skills on Improving Teacher Performance in State Junior High Schools in Tanjung Lubuk District - Ummi Atiah; Tri Widayatsih; Pahlawan Pahlawan (International Journal of Educational Research, 2025)
This research was conducted with the aim of finding out and analyzing 1). To find out and analyze the influence of visionary leadership on teacher performance in State Junior High School in Tanjung Lubuk District 2). To find out and analyze the influence of communication skills on teacher performance in State Junior High Schools in Tanjung Lubuk District 3). To find out and analyze the influence of visionary leadership and communication skills on teacher performance in State Junior High School in Tanjung Lubuk District. This study uses a quantitative method with a type of correlational research. The sample of this study was carried out in 4 State Junior High Schools in Tanjung Lubuk District with a total of 53 teachers. Data collection techniques use questionnaires and documentation. The data were analyzed using correlation analysis and multiple regression techniques. This can be seen in school leaders who have a clear vision and are able to inspire teachers to contribute 27.2% to improving their performance, while the remaining 72.8% are influenced by other elements outside this study. In this study, the influence of communication skills on teacher performance was 68.7% and 31.3% influenced by other factors. The overall results of this study show that there is an influence of visionary leadership and communication skills together on the performance of State Junior High School teachers in Tanjung Lubuk District by 74.1% and 25.9% influenced by other factors.